Pengaruh Pelatihan Berbasis Kompetensi Terhadap Produktivitas Keterampilan Ibu Rumah Tangga (Studi Kasus di UPTD Balai Latihan Kerja Kabupaten Banyuasin) - Oktaviyani, Henny; Shalahuddin, M.; Oktavianti, Santi; Rahmania, Vanesha; Patur, Patur (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2024)
The company makes planned efforts to enhance the knowledge, skills, and abilities of its employees through training. With the right training, organizations are expected to improve employee work efficiency to achieve the set work objectives. This study aims to analyze the impact of Competency-Based Training on the Productivity of Housewives' Skills (Case Study at UPTD Balai Latihan Kerja Kabupaten Banyuasin). The sampling technique used is saturated sampling, where the entire population can be sampled, amounting to 100 people. Simple regression analysis is used to process the data. Simple regression analysis is used to calculate the extent of the influence of the dependent variable on the independent variable. Based on the results and discussions that have been conducted, several conclusions can be drawn, namely that the training variable partially has a positive and significant effect on the productivity of Housewives participating in the UPTD Balai Latihan Kerja Kabupaten Banyuasin training.